Gaṇatāntrika āndolane aikya - Rīẏāja, Ālī (Anupama : ekamātra paribeśaka, Bukasa eṇḍa Pirioḍikyālasa, 1983)
Articles on the need for unity among the democratic forces in Bangladesh, with reference to the working of political parties.